Overexpression and Purification of Gracilariopsis chorda Carbonic Anhydrase (GcCAα3) in Nicotiana benthamiana, and Its Immobilization and Use in CO2 Hydration Reactions - Md Abdur Razzak; Dong Wook Lee; Dong Wook Lee; Junho Lee; Inhwan Hwang; Inhwan Hwang (Frontiers in Plant Science, 2020)
Carbonic anhydrase (CA; EC 4.2.2.1) is a Zn-binding metalloenzyme that catalyzes the reversible hydration of CO2. Recently, CAs have gained a great deal of attention as biocatalysts for capturing CO2 from industrial flue gases owing to their extremely fast reaction rates and simple reaction mechanism. However, their general application for this purpose requires improvements to stability at high temperature and under in vitro conditions, and reductions in production and scale-up costs. In the present study, we developed a strategy for producing GcCAα3, a CA isoform from the red alga Gracilariopsis chorda, in Nicotiana benthamiana. To achieve high-level expression and facile purification of GcCAα3, we designed various constructs by incorporating various domains such as translation-enhancing M domain, SUMO domain and cellulose-binding domain CBM3. Of these constructs, MC-GcCAα3 that had the M and CBM3 domains was expressed at high levels in N. benthamiana via agroinfiltration with a yield of 1.0 g/kg fresh weight. The recombinant protein was targeted to the endoplasmic reticulum (ER) for high-level accumulation in plants. Specific and tight CBM3-mediated binding of recombinant GcCAα3 proteins to microcrystalline cellulose beads served as a means for both protein purification from total plant extracts and protein immobilization to a solid surface for increased stability, facilitating multiple rounds of use in CO2 hydration reactions.